La salina de San Blas (Óndores, Junín). Una reconsideración sobre su extensión y cronología - Saez Diaz, Sergio (2024)
This article discusses the available evidence on the San Blas salt spring from the first works of Ramiro Matos, Daniel Morales and the results of the excavations carried out by the authors in 2017. Based on these evidences, the authors propose a new approach on the extension and chronological sequence of the settlement, as well as the hypothesis that San Blas functioned as a multi-ethnic site based on the theory of "vertical control of ecological floors" through economic enclaves.